Recensiones - J. E. T. P.; S. M. A.; X. X; Mantilla, Sebastián; Irure, Agustín (ECA: Estudios Centroamericanos, 1974)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 29, No. 310-311, 1974: 641-645.